The Role of Family Characteristics for Students' Academic Outcomes: A Person‐Centered Approach. Issue 4 (17th April 2017) - Häfner, Isabelle; Flunger, Barbara; Dicke, Anna‐Lena; Gaspard, Hanna; Brisson, Brigitte M.; Nagengast, Benjamin; Trautwein, Ulrich
Abstract : Using data from 1, 571 ninth‐grade students ( M age = 14.62) from 82 academic track schools in Germany and their predominantly Caucasian middle‐class parents, configurations of different family characteristics reported by parents were investigated. Latent profile analyses considering academic involvement, family interest, parents' self‐concept, child's need for support, and parents' time and energy identified average, indifferent, motivated and engaged, motivated and disengaged, and involved families. Cross‐sectional and longitudinal associations with students' motivational (self‐concept, effort, and interest) and achievement outcomes (achievement test and grades) in math were analyzed. Students from families classified as motivated and disengaged showed higher initial levels motivation and achievement. Over 5 months, these students also showed an increase in self‐concept and higher achievement than students from other family types.